Kewajiban Dan Tanggung Jawab Hukum Perdata Dalam Perlindungan Privasi Data Pasien Dalam Layanan Kesehatan Digital - Mohamad Rizky Ardiansyah; Restu Ardiana (LPPM Universitas Sains dan Teknologi Komputer, 2023)
This journal article discusses the role of civil legal obligations and responsibilities in the context of protecting patient data privacy in digital health services which are increasingly penetrating the modern medical world. The main objective of this article is to analyze the legal framework that regulates the protection of patient data privacy in the digital environment, understand the civil legal obligations that regulate digital health service providers in protecting patient data, and analyze the rights and obligations of patients in the context of protecting patient data privacy in services. digital health. The approach method in this research involves analysis of various relevant rules and regulations, such as the Personal Data Protection Law and medical professional ethical guidelines. The results of this study reveal that compliance with patient data privacy regulations in digital healthcare varies, and there is an urgent need for increased legal understanding and awareness among stakeholders, including healthcare providers, application developers, and patients.